Emergency Splenectomy in a patient with primary immune thrombocytopenia and hemoperitoneum - Liermis Michael Dita Salabert; José Eduardo Consuegra Díaz; Carlos Jaime Geroy (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Primary immune thrombocytopenia is an acquired autoimmune disease, with a very variable clinical course, which causes an accelerated destruction by antibodies and an impaired platelet production. A case of a 40 year-old female patient of rural origin with a history of mitral stenosis and atrial fibrillation, diagnosed two months prior to her admission to the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos, is presented. She attended the hospital with ecchymosis and petechiae on the lower and upper limbs. After confirming a severe thrombocytopenia (5x109/ l), she was admitted to the Hematology Department. Possible primary immune thrombocytopenia was found. During her stay in the hospital, her clinical condition was complicated by hemoperitoneum. The patient underwent surgery which confirmed the presence of four liters of blood in the abdominal cavity with few clots, bleeding and fissure in the left ovary and adherent clots. An early clamping of the splenic artery, evacuation of the hemoperitoneum, left adnexectomy, splenectomy and resection of accessory spleen were performed. The patient progressed satisfactorily.